The importance of paying attention to anthropometrics in the selection athletes - Putra, R. B. A.; Rahayu, T.; Kasmini, W.; Sulaiman (Advances in Social Science, Education and Humanities Research, 2019)
The purpose of this study is to analyze the importance of the ideal anthropometric exercise so that it can support the effectiveness and efficiency of the training process. Systematic review method of 38 articles to identify problems, collect information, and conclusions. The review results that there are certain anthropometric characteristics in the form of height, weight, body size, fat in each volleyball, gymnastics, basketball, football, triathletes and cyclists and swimming. This shows that physiologically the anthropometrics of athletes support their best performance in each of the sports characters involved. The size of body posture is the nature of the athlete. During the process of exercise training does not have much effect on the proportion of body size. Conclusions that anthropometrics are very important in analysis to provide benefits in developing one`s potential, especially in the performance